THE FUNCTION OF CHILDREN SOCIAL RESEARCH AS A RECOMMENDATION TO JUDGES IN DECIDING JUNEVILE CRIMINAL JUSTICE CASES - Asmawati, Hermi (CV. Era Digital Nusantara, 2022)
Children who commit crimes need to get special treatment that is different from the process of adults. This is because the situations and conditions in the legal process make children who are dealing with the law take up a lot of their time to interact normally with other people, so that it will have an impact on their psychological disorders. Bapas plays an important role in accompanying Children in Conflict with the Law through Social Advisor who carry out Social Research, guidance, supervision, and assistance to Children inside and outside the criminal justice process. This study aims to analyze one of these functions, namely Social Research as one of the Judge's recommendations in deciding juvenile justice cases. The results of the study conclude that the Social Research Report is of great benefit to judges in making a decision on a case appropriately and fairly. Even if the judge's decision does not take into account the judge's decision, it can be stated that the decision is null and void.